Studi Fenomenologi Persepsi Masyarakat Dalam Penerapan Protokol Covid-19 - Dewi, Ratna; Apriliani, Irina (REAL in Nursing Journal, 2021)
Background: Corona Virus Disease 2019 is an infectious disease caused by acute respiratory syndrome coronavirus 2 (Sars-CoV-2). The research objective explores how the public's perception of the application of Covid-19. Methods: Qualitative research methods with a phenomenological approach. The research informants were taken by purposive sampling, totaling 10 people in the Tanjung Bajure Market Area, Sungai Penuh City. The data were processed and analyzed using the Colaizzi method. Result: The results of the study contained several themes, namely, public perception about Covid-19, perceptions of compliance with self-protection from Covid-19 transmission, lack of compliance with the Covid-19 protocol and lack of understanding of Corona Virus Disease 2019. Conclusion: It can be concluded that the public perception of the application of Covid-19 in the Tajung Bajure market area, the river city is full of different public opinions, most people understand the importance of protecting themselves from Covid-19, but many people still have doubts about the existence of Covid-19 because of a lack of willingness facilities make participants less complying with the Covid-19 protocol.Keywords: Public perception, Application of the Covid-19 Protocol